Kontribusi Delapan Standar Nasional Pendidikan terhadap Pencapaian Prestasi Belajar - Sabar Budi Raharjo (Jurnal Pendidikan dan Kebudayaan, 2014)
National education standards is a means to ensure the quality of educational services. School administrators must fulfill minimum standards in helping students to achieve learning target. The purpose of this study was to determine the achievement of national education standards and the extent to which they contribute to eight national education standards towards the learning achievemen of high school students. The research method is a survey. The results showed that first, among the achievement of eight national education standards, educational facilities and infrastructures standards, process standards competency standards and education professional standards were considered low. Second, the eight national education standards contribute less significant to student national examination score. This means that successful learning achievement is determined by other factors, both internal and external, such as motivation, interest, parental background, school environment. From the eight standards, teacher and education personnel standard give significant influence to national students exam results. The first conclusions is that, four standards with below average accreditation credits are educational facilities and infrastructures standards, process standards, competency standards, and education professional standards. Secondly, the contribution of eight national standards of education is still relatively less and other factors are needed in order to improve the students’ learning achievement.